Validation of a Liquid Chromatography/Tandem Mass Spectrometry Assay for the Quantification of Plasma Dihydroartemisinin - Dona Arlinda; Intan Sari Oktoberia; Muhammad Karyana (Cell and BioPharmaceutical Institute, 2021)
Background: Insufficient plasma level of dihydroartemisinin (DHA) can select resistance and will further hinder malaria elimination program. We investigated clinical applicability of a validated liquid chromatography/tandem mass spectrometry (LC-MS/MS) assay to quantify plasma concentration of DHA in healthy subjects from a single oral administration of fixed dose combination of Dihydroartemisinin-Piperaquine.Materials and Methods: Micro-elution solid-phase extraction in a 96-well plate format was used to prepare the samples. DHA separation happened in Acquity UPLCTM BEH C18 column (50 × 2.1 mm, 1.7 µm). Mobile phase was a mixture of acetonitrile-ammonium acetate 10 mM pH 3.5 (50:50, v/v) at 0.3 mL/minute flow rate. Waters Acquity UPLC™ H-Class system coupled with triple quadruple mass spectrometry in positive electrospray ionization mode was used for detection. The internal standard was a stable isotope labelled DHA.Results: Calibration curve was linear with a correlation coefficient >0.995 over a concentration range of 1–1,000 ng/mL. Bias and variation for accuracy and precision were in the range of 15% (20% at the lower limit of quantification). Using 5 µL sample, lower limit of quantification was 1 ng. Matrix effect was less than 15%. The method was successfully applied to investigate the pharmacokinetics of DHA from five healthy subjects, although carry over and the role of anticoagulants were not tested.Conclusion: The LC-MS/MS assay for the quantification of plasma DHA was validated for selectivity, linearity, lower limit of quantitation, accuracy, precision, matrix effect and stability. Although clinical applicability was demonstrated, this method was to be improved to address the not-tested validation parameters.Keywords: dihydroartemisinin, liquid chromatography/tandem mass spectrometry assay (LC-MS/MS), malaria, Indonesia